2004
DOI: 10.1111/j.1432-1033.2004.04240.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential involvement of protein kinase C alpha and epsilon in the regulated secretion of soluble amyloid precursor protein

Abstract: We investigated the differential role of protein kinase C (PKC) isoforms in the regulated proteolytic release of soluble amyloid precursor protein (sAPPa) in SH-SY5Y neuroblastoma cells. We used cells stably transfected with cDNAs encoding either PKCa or PKCe in the antisense orientation, producing a reduction of the expression of PKCa and PKCe, respectively. Reduced expression of PKCa and/or PKCe did not modify the response of the kinase to phorbol ester stimulation, demonstrating translocation of the respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 39 publications
5
32
0
Order By: Relevance
“…Thus, part of the effect could also be mediated by induction of PKC⑀ by PMA. Decreased expression of PKC⑀ also reduces cholinergic regulation of sAPP␣ levels (34), which is consistent with the theory that sAPP␣ and A␤ compete for a limited pool of APP. Thus, in cells in which APP is rate-limiting, direct or indirect activation of ␣-secretase by PKC⑀ could also reduce A␤ levels.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, part of the effect could also be mediated by induction of PKC⑀ by PMA. Decreased expression of PKC⑀ also reduces cholinergic regulation of sAPP␣ levels (34), which is consistent with the theory that sAPP␣ and A␤ compete for a limited pool of APP. Thus, in cells in which APP is rate-limiting, direct or indirect activation of ␣-secretase by PKC⑀ could also reduce A␤ levels.…”
Section: Discussionsupporting
confidence: 87%
“…In vitro studies have demonstrated that different PKC isoforms play distinct roles in APP processing. PKCa is specifically involved in phorbol ester-induced sAPPa release, while PKCe is involved in coupling cholinergic receptors with APP metabolism (12). In vivo studies using a guinea-pig model with constitutive overactivation of PKCa and -b isoforms have shown an increase in sAPPa production, indicating that these isoforms are key regulators of a -secretory APP processing (13).…”
Section: Role Of Pkc In Ab Generationmentioning
confidence: 99%
“…One of these functions promotes the cleavage and release of soluble signaling proteins that are ini-tially synthesized as membrane-spanning precursors. In addition to NRG1, other proteins released upon PKC activation include epidermal growth factor, transforming growth factor-␣, amyloid precursor protein, L-selectin, and interleukins (1,(37)(38)(39)(40)(41)(42)(43). We hypothesize that neurotrophic factors induce the cleavage and release of NRG1 from pro-NRG1 through PKC activation.…”
mentioning
confidence: 99%